Successful Treatment of Cluster-Like Aneurysm Associated with Coarctation of the Aorta - Aoki, Isao; Koyanagi, Katsushi; Mizuno, Asatoshi; Kurosawa, Hiromi (Japanese Journal of Cardiovascular Surgery, 2001)
A 19-year-old woman with thoracic aortic aneurysm complicating coarctation of the aorta was treated successfully. Aortography and 3D-CT showed the thoracic aortic aneurysm resembling a cluster of grapes. Coarctation of the aorta was seen between the aortic aneurysm and the descending aorta, and there was a 40mmHg pressure gradient between the ascending aorta and the descending aorta. At operation, the wall of the cluster-shaped saccular aortic aneurysm was very thin. We could see the blood flow through the wall, and we thought this patient was at high risk of ruptured aneurysm. The aneurysm was excised and replaced by a Hemashield tube graft, 16mm in diameter. The left subclavian artery was also constructed using a Hemashield tube graft, 8mm in diameter. Ruptured aneurysm in a patient with aortic aneurysm complicated by coarctation of the aorta has a high risk of death, so surgical intervention should be performed as soon as possible.